2021
DOI: 10.29356/jmcs.v65i4.1512
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Various Physicochemical Properties of Walnut Oil from Different Areas of Northern Kpk, Pakistan

Abstract: Abstract. In this study, the physicochemical properties of walnut (Juglans regia L.) oils collected from different sites in Khyber PakhtoonKhwa (KPK), Pakistan were investigated. The obtained walnut oils showed variation in viscosity, surface tension, density, acid, saponification, and iodine values. The oil obtained from the Madyan (Sample E) showed the lowest density (0.981 g/cm3), surface tension (34.76×10-3 N/m), viscosity (15.0595 cp) saponification values 84.15 (mg KOH/g of oil) and acid value 3.5 (mg KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Upon recent reports, walnuts appear to be gaining considerable attention for their beneficial health properties [10], including antidepressant, anti-inflammatory, as well as antidiabetic activities [11], primarily due to the availability of bioactive compounds such as phytosterols and plant polyphenols [12][13][14][15][16]. In addition, consuming walnuts has been associated with many health benefits, as they are an excellent source of omega-3 fatty acids, with a percentage up to 10% [17], vitamin E [18][19][20], as well as other antioxidants that are involved in cardiovascular health and reducing cancer cell growth [21].…”
Section: Introductionmentioning
confidence: 99%
“…Upon recent reports, walnuts appear to be gaining considerable attention for their beneficial health properties [10], including antidepressant, anti-inflammatory, as well as antidiabetic activities [11], primarily due to the availability of bioactive compounds such as phytosterols and plant polyphenols [12][13][14][15][16]. In addition, consuming walnuts has been associated with many health benefits, as they are an excellent source of omega-3 fatty acids, with a percentage up to 10% [17], vitamin E [18][19][20], as well as other antioxidants that are involved in cardiovascular health and reducing cancer cell growth [21].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that thanks to the high PUFA content, walnuts contribute to reducing the risk of heart disease by lowering the level of LDL cholesterol and increasing the level of HDL cholesterol [4]. Walnut oil is very popular in the food industry due to its favorable profile of fatty acids, which are essential in the prevention of diseases of the nervous system [5]. Consumers are aware of the healthpromoting potential of this category of plant raw materials and include them in their diet.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of modern medicine, a large number of pharmacological and clinical tests have found that walnuts have various therapeutic effects, such as enhancing immunity, improving memory, preventing cardiovascular diseases, and regulating abnormal lipid metabolism [15]. Yasir Uddin et al found that walnut oil obtained from Madyan had similar properties to olive oil with high concentrations of oleic acid (41%) and linoleic acid (9%) [16]. Ullah, S. F. et al found that walnut protein isolate showed excellent physicochemical and functional properties for use in food or industry product development [17].…”
Section: Introductionmentioning
confidence: 99%